2019
DOI: 10.1002/ptr.6311
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of magnolol on oxaliplatin‐induced intestinal injury in mice

Abstract: Oxaliplatin (OXL) is the first line treatment therapy for gastrointestinal (GI) cancers and often combines with other chemotherapy. However, few reports have studied on its GI toxicity. Magnolol (MG), one of the mainly active constituents in Magnolia, has been reported to treat digestive diseases. Therefore, the purpose of this study is to evaluate the intestinal protective effect of MG in OXL treatment group. OXL administration mice showed body weight loss, diarrhea, and intestinal damage characterized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
(58 reference statements)
2
17
0
Order By: Relevance
“…Our data showed that magnolol decreased the levels of MDA, PC and 8-OHdG in serum or liver, which demonstrated that magnolol might modulate the antioxidant status of Linwu ducklings. Xia [50] found that magnolol suppressed oxidative stress in the small intestinal tissue of mice induced by oxaliplatin, which supported what was found in the present experiment. The mechanism of antioxidative effect with magnolol was uncertain.…”
Section: Plos Onesupporting
confidence: 92%
“…Our data showed that magnolol decreased the levels of MDA, PC and 8-OHdG in serum or liver, which demonstrated that magnolol might modulate the antioxidant status of Linwu ducklings. Xia [50] found that magnolol suppressed oxidative stress in the small intestinal tissue of mice induced by oxaliplatin, which supported what was found in the present experiment. The mechanism of antioxidative effect with magnolol was uncertain.…”
Section: Plos Onesupporting
confidence: 92%
“…(2) Increased abundance of Firmicutes and reduced abundance of Bacteroidetes [31,34,35], although conflicting results had also been reported [30,40,41]; (3) increased abundance of Gram-negative (G-) bacteria, including potential pathogenic microbes such as E. coli and Pseudomonas, and decreased abundance of Gram-positive (G+) bacteria, such as Bifidobacterium and Lactobacillus [7,27,28,[34][35][36][37]39,[41][42][43]. In addition, some intestinal bacteria were found translocated to mesenteric lymph nodes and spleen [38].…”
Section: Bacteroidetes Firmicutesmentioning
confidence: 99%
“…The changes caused by oxidative stress were inhibited; there was an increase in the activity of SOD, glutathione peroxidase (GPx) and the increase in the level of glutathione, as well as the decrease in the level of NF-κB and pro-inflammatory cytokines. Additionally, magnolol contributed to the restoration of the normal intestinal microflora, disturbed by the administration of oxaliplatin [ 136 ].…”
Section: Magnolol In Diabetes and Its Complicationsmentioning
confidence: 99%